Death as Initiation (Rebirth) - Mohsen Botlab Akbarabadi; Masoumeh Barsam (مجله مطالعات ایرانی, 2016)
Abstract Human existence lies in the heart of existentialism. This school of thought deals with the challenges of human responsibility and the possibility of improvement and progress of human life. Centuries before the advent of existentialism in the West, however, the Iranian prophet, Zoroaster, believed in Ahoura Mazda and human values and followed such aims as human beings progress toward his ethical treats and prosperousness. This study tends to comparatively analyze doctrines of existentialism and Zoroastrianism, and describes such key concepts as reality of human existence, authority and freedom, free will, responsibility, refusing predetermined fate, recommending endeavor and avoiding solitude. The study illustrates that there are similarities and differences between these two schools of thought. The issue of human existence and its relation to the world have been wisely expressed in Zoroastrianism, centuries before existentialism. In fact, Zoroaster expressed the same thing as the existentialism asserted in the twentieth century. In order to carry this comparative study historical and library documents were examined. The method of research was descriptive-analytical.